Massa argilosa incorporada com metacaulim para fabricação de tijolos refratários - CRUZ JÚNIOR, Roberto de Sousa (2019)
The present work evaluated the effect of metakaolin incorporation in a clay mass composed of two types of clay, a “strong” clay and a “weak” clay, aiming at the production of refractory bricks. Firstly, the raw materials were disaggregated and homogenized. Subsequently, the materials were characterized mineralogical by X-Ray Diffraction (XRD), chemistry by X-Ray Fluorescence (XRF) also Fourier Transform Infrared Spectroscopy (FTIR) and Thermogravimetry (TG) also Thermogravimetry Derivative (DTG) by thermal analysis. After that, were mixed three ceramic formulations, clayey mass without the addition of metakaolin, clayey mass with 5% of metakaolin and clayey mass with 10% of metakaolin. Subsequently, 42 specimens (SM’s) were made by uniaxial pressing at 20 MPa. Moreover, the SM's were burned at temperatures of 950 ºC and 1050 ºC with a 2 hour burning landing. After the firing process, the apparent specific mass, water absorption (WA) and flexural rupture stress (FRS) of the burnt pieces were determined. The formulation with the addition of 10% by weight of metakaolin burned at a temperature of 1050 ºC showed promising results, with FRS of 9.37 MPa.